66‐4: Effects of Display Curvature and Lateral Viewing Position on Spatial Presence and Image Quality for 55″ TVs. Issue 1 (May 2016) - Park, Sungryul; Yi, Jihhyeon; Choi, Donghee; Lee, Songil; Kyung, Gyouhyung; Choi, Byeonghwa; Lee, Ja Eun; Lee, Seungbae
Abstract : The current study examined the effects of display curvature and lateral viewing position on spatial presence and image quality for 55" TVs. We considered four curvature‐radii (2300mm, 4000mm, 6000mm, and flat) and five lateral viewing positions P1 ‐P5 (0mm, 350mm, 700mm, 1050mm, and 1400mm from the center position). Viewing distances were fixed at 4000mm. A total of 56 participants (14 individuals per display curvature) watched 5‐min video footages, each time at a randomly selected position. Spatial presence (SP) was reported on the ITC Sense of Presence Inventory (ITC‐SOPI), and perceived image quality (IQ) on the Single Stimulus Continuous Quality Evaluation (SSCQE). Of all curvature × position conditions, P1 at the 4000mm curvature provided the highest SP. Across curvatures, SPs were higher at P1 and P2 than at any other viewing positions, and IQs were higher at P1 than at P3, P4, or P5 . Under the assumption that one‐to‐five viewer conditions are equally important, the 4000mm curvature is likely to provide the highest SP, and the flat condition the highest IQ. Under an additional assumption that SP and IQ are equally important, the 4000mm curvature is likely to be the best for the one‐to‐four‐viewer conditions, while the 6000mm curvature is for the five‐viewer condition.